Some observations on magnesium in cerebrospinal fluid. Issue 6 (November 1965) - Pallis, Christopher; Macintyre, Iain; Anstall, Harold
Abstract : Investigation of 67 patients with neurological disorders (excluding meningitis) showed a mean level of Mg in cerebrospinal fluid of 1·93 ± 0·03 mEq./l. These figures are significantly lower than earlier figures published in the literature. Patients with polyradiculo-neuritis do not show the fall in cerebrospinal fluid Mg levels reported in cases of infective meningitis. The level of Mg in cerebrospinal fluid is maintained in the presence of low levels of plasma Mg.